Oogenesis of bester hybrids (female Huso huso (Linnaeus, 1758) × male Acipenser ruthenus (Linnaeus, 1758) during the inter‐spawning period while cultured in a recycling system. (November 2015) - Piyanova, S. V.; Filippova, O. P.; Zuevskiy, S. E.
Summary: The study aims were to determine the dynamic changes in oocyte characteristics in the ovaries of two hybrids of beluga and sterlet under controlled conditions. The study was carried out between 2010 and 2012, with fish approaching their maturation period in captivity. Duration of the inter‐spawning period lasted from 10 to 12 months for the two hybrids raised at temperatures of 20–21°C. The oocyte envelopes and their characteristics were studied using histology. The oocyte envelope layers showed inter‐hybrid differences in growth and structural characteristics. The bester eggs can be determined by their envelope thickness compared to most other sturgeon eggs. Duration of various stages of the individual oogenetic development and envelope formation is described in bester hybrids. These were similar to the oogenesis for both of the other hybrid forms and those observed in the pure sturgeon species.